Nondestructive Assay of Nuclear Materials for Safeguards and Security - Geist, William H.; Santi, Peter A.; Swinhoe, Martyn T.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access book describes the nondestructive assay techniques that are used for the measurement of nuclear material (primarily uranium and plutonium) for nuclear material accountancy purposes. It is a substantial revision to the so-called PANDA manual that has been a standard reference since its publication in 1991. The book covers the origin and interactions of gamma rays and neutrons as they affect nuclear measurements and also describes the theory and practice of calorimetry. The book gives a description of many instruments based on these techniques that are applied in the field. Although the basic physics has not changed since PANDA was first published, the last thirty years have seen many advances in analysis methods, instrumentation, and applications. The basic descriptions of the origin and interactions of radiation have been updated and include newer references. There have been extensive revisions of the description of gamma detection methods, attenuation correction procedures, and analysis methods, including for the measurement of uranium enrichment and the determination of plutonium isotopic composition. Extensive revisions and additions have also been made to the description of neutron detectors and to the explanation of neutron coincidence techniques. The chapter on neutron multiplicity techniques is a new addition to this edition. The applications of gamma and neutron techniques have been completely overhauled to remove obsolete systems and to include many current applications. The values of, and references to, nuclear data have been updated. This updated edition is an essential reference for academic researchers and practitioners in the field. This is an open access book.
Chapter 1. The Role of Nondestructive Assay in Safeguards, Security, and Safety -- Chapter 2. The Origin of Gamma Rays -- Chapter 3. Gamma-Ray Interactions with Matter -- Chapter 4. Gamma-Ray Detectors -- Chapter 5. Instrumentation for Gamma-Ray Spectroscopy -- Chapter 6. Attenuation Correction Procedures -- Chapter 7. General Topics in Passive Gamma-Ray Assay -- Chapter 8. The Measurement of Uranium Enrichment -- Chapter 9. Plutonium Isotopic Composition by Gamma-Ray Spectroscopy -- Chapter 10. Gamma-Ray NDA Applications & Techniques -- Chapter 11. Densitometry -- Chapter 12. X Ray Fluorescence -- Chapter 13. The Origin of Neutron Radiation -- Chapter 14. Neutron Interactions with Matter -- Chapter 15. Neutron Detectors -- Chapter 16. Principles of Singles Neutron Counting -- Chapter 17. Principles of Neutron Coincidence Counting -- Chapter 18. Principles of Neutron Multiplicity -- Chapter 19. Passive Neutron Instrumentation and Application -- Chapter 20. Active Neutron Instrumentation and Applications -- Chapter 21. Spent Fuel Measurements -- Chapter 22. Perimeter Radiation Monitors -- Chapter 23. Principles of Calorimetric Assay -- Chapter 24. Calorimetric Assay Instruments.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Nuclear physics; Nuclear engineering; Refuse and refuse disposal; Measurement; Measuring instruments; Security systems; Nuclear Physics; Nuclear Energy; Waste Management/Waste Technology; Measurement Science and Instrumentation; Security Science and Technology